The nurse's performance in front of the safety of the home patient (Research, Society and Development, 2022)
Objective: To analyze the role of nurses, their importance and attributions within the home environment. Method: qualitative documentary research was adopted, comparing materials and method, with data obtained from LILACS, BDENF, IBECS and MEDLINE, in which articles in English, Spanish and Portuguese were included, from 2009 to 2021. Results: 17 articles were analyzed, after excluding those that would not be used. Among them, it was identified that the role of nurses in home care encompasses much more than performing procedures. The nurse becomes the manager of all care, being the facilitator between the family and the care provided. Conclusion: the role of nurses in the home environment is something quite broad, as nurses do not participate only in practical procedures. He takes care of all the management that involves that patient, from hospital discharge to home admission, it is up to this professional to initiate care guidelines from the beginning of care, always clarifying the family's doubts, and explaining what behaviors were planned for the patient. This has the power to reduce their anxieties, so that together they can offer safe and continuous assistance.